2006
DOI: 10.1245/aso.2006.04.040
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Technical Complications on Postoperative Outcome and Survival After Esophagectomy

Abstract: Although immediate postoperative outcome and hospital mortality rates were increased, no effect on long-term survival was seen in patients with complications related to errors in surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 43 publications
4
62
2
3
Order By: Relevance
“…6,10,45 Moreover, there is mounting evidence that states of systemic inflammation can accelerate the progression of metastatic tumor development. [23][24][25]38,39 The present data demonstrate that these two phenomena are inter-related, and that activated neutrophils represent a third cellular participant in this process. In this study, a physiologically relevant in vivo model of the early stages of hematogenous metastasis was developed using fluorescence intravital microscopy to monitor the trafficking of tumor cells in the liver vasculature.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…6,10,45 Moreover, there is mounting evidence that states of systemic inflammation can accelerate the progression of metastatic tumor development. [23][24][25]38,39 The present data demonstrate that these two phenomena are inter-related, and that activated neutrophils represent a third cellular participant in this process. In this study, a physiologically relevant in vivo model of the early stages of hematogenous metastasis was developed using fluorescence intravital microscopy to monitor the trafficking of tumor cells in the liver vasculature.…”
Section: Discussionmentioning
confidence: 74%
“…21,22 Several reports from clinical series have raised the possibility that inflammatory consequences resulting from postsurgical complications may influence cancer recurrence. [23][24][25] Evidence from studies of other malignancies such as colorectal carcinoma have shown that proinflammatory cytokines such as TNFa and IL-1b increase tumor cell adhesion to endothelial cells in vitro and in vivo, largely by upregulating the expression of cell adhesion molecules such as selectins on the endothelial surface. 26 In addition, soluble inflammatory mediators have been shown to increase the expression of selectin ligands on cancer cells.…”
mentioning
confidence: 99%
“…Together, the combination of acute systemic inflammatory stimuli with high numbers of CTCs presents a fertile ground for the initiation of metastasis (3). The clinical evidence linking postoperative complications and high CTC numbers to poor oncologic outcomes is abundant (30)(31)(32)(33)(34). This study contends that neutrophils, as key effectors of the acute systemic inflammatory reaction, play a functional role to promote the implantation of CTCs and, thus, facilitate metastatic spread to distant organs such as the liver.…”
Section: Introductionmentioning
confidence: 98%
“…A correta dissecção do estômago associada ou não à manobra de Kocher permite a confecção de um tubo gástrico de dimensões capazes de atingir a região cervical, conferindo condições ótimas para anastomose segura 29,31,60 . A preferên-cia pela região cervical deve-se ao fato da benignidade das fístulas neste plano anatômico 20,21,22 . No mesmo nível de importância, é prioritário o manejo adequado do paciente no período perioperatório, evitando a hipotensão e seu impacto negativo na perfusão sistêmica e oxigenação tecidual, sendo relevante a manutenção de adequado volume intravascular e evitando o uso de drogas vasopressoras 22 .…”
Section: Tabela 1 -Dados Dos Dois Grupos Do Estudounclassified
“…Curiosamente, outras séries inferem que a mortalidade a longo prazo não foi afetada pelo índice de intercorrências técnicas 3,5,21 .…”
Section: Tabela 1 -Dados Dos Dois Grupos Do Estudounclassified